Attendance and Risk of Exclusion among Scottish Secondary School Pupils with Additional Support Needs - Treanor, Morag; Troncoso, Patricio; Lee-Shield, Bethany; Behrens, Silvia; Williamson, Lee; MacIntyre, Cecilia (International Journal of Population Data Science, 2025)
We seek to demonstrate differences in attendance across pupils with and without additional support needs (ASN), accounting for broader categories of as well as specific types of ASN. The aim is to provide more nuanced insights into the risks for educational absence and determine whether certain ASN are associated with specific types or patterns of absence. We first compared the differences in average attendance and absence across pupils with and without ASN using standardised effect sizes. ASN categories differentiate by health needs, social and emotional needs, family circumstances, learning environment, and other types of need. Following the descriptive analysis, we ran a latent class analysis to identify underlying patterns of non-participation within pupils with ASN. This is followed by a binomial logistic regression to predict class membership of pupils based on their specific ASN. We find distinct gaps in attendance and absence behaviour between pupils with and without ASN and significant effect sizes for these differences. The latent class analysis reveals that pupils with health needs and issues relating to the learning environment are more likely to have low authorised and unauthorised absence, as well as a low risk of exclusion. In contrast, pupils with social and emotional needs and experiences of adverse family circumstances are more likely to have higher absence and a greater risk of exclusion. While ASN is regularly considered as an adverse influence on attendance, less differentiation has been made between different support needs and types of educational absence. Our results help identify these differences and inform dedicated support and interventions for pupils with ASN.